Design, Synthesis and Anti-Tumor Activity of Novel Benzimidazole-Chalcone Hybrids as Non-Intercalative Topoisomerase II Catalytic Inhibitors - Wei Zhou; Wenjin Zhang; Yi Peng; Zhi-Hong Jiang; Lanyue Zhang; Zhiyun Du (Molecules, 2020)
Chemical diversification of type II topoisomerase (Topo II) inhibitors remains indispensable to extend their anti-tumor therapeutic values which are limited by their side effects. Herein, we designed and synthesized a novel series of benzimidazole-chalcone hybrids (BCHs). These BCHs showed good inhibitory effect in the Topo II mediated DNA relaxation assay and anti-proliferative effect in 4 tumor cell lines. 4d and 4n were the most potent, with IC50 values less than 5 μM, superior to etoposide. Mechanistic studies indicated that the BCHs functioned as non-intercalative Topo II catalytic inhibitors. Moreover, 4d and 4n demonstrated versatile properties against tumors, including inhibition on the colony formation and cell migration, and promotion of apoptosis of A549 cells. The structure-activity relationship and molecular docking analysis suggested possible contribution of the chalcone motif to the Topo II inhibitory and anti-proliferative potency. These results indicated that 4d and 4n could be promising lead compounds for further anti-tumor drug research.